It is rocket science – why dietary nitrate is hard to 'beet'! Part II: further mechanisms and therapeutic potential of the nitrate‐nitrite‐NO pathway. (6th May 2016) - Mills, Charlotte Elizabeth; Khatri, Jibran; Maskell, Perry; Odongerel, Chimed; Webb, Andrew James
Abstract : Dietary nitrate (found in green leafy vegetables such as rocket and in beetroot) is now recognized to be an important source of nitric oxide, via the nitrate‐nitrite‐NO pathway. Dietary nitrate confers several cardiovascular beneficial effects on blood pressure, platelets, endothelial function, mitochondrial efficiency and exercise. Having described key twists and turns in the elucidation of the pathway and the underlying mechanisms in Part I, we explore the more recent developments which have served to confirm mechanisms, extend our understanding, and discover new properties and potential therapeutic uses of the pathway in Part II. Even the established dependency on low oxygen states for bioactivation of nitrite has recently been challenged. Dietary nitrate appears to be an important component of 'healthy diets', such as the DASH diet to lower blood pressure and the Mediterranean diet, with its potential to lower cardiovascular risk, possibly through beneficial interactions with a range of other constituents. The World Cancer Research Foundation report strong evidence for vegetables including spinach and lettuce (high nitrate‐containing) decreasing cancer risk (mouth, pharynx, larynx, oesophagus and stomach), summarized in a 'Nitrate‐Cancer Risk Veg‐Table'. The European Space Agency recommends that beetroot, lettuce, spinach and rocket (high‐nitrate vegetables) are grown to provide food for long‐term space missions. Nitrate, an ancient component of rocket fuel, could support sustainable crops for healthy humans.